2000
DOI: 10.1038/sj.ijo.0801461
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index during childhood, adolescence and young adulthood in relation to adult overweight and adiposity: the Fels Longitudinal Study

Abstract: BACKGROUND: Childhood overweight develops during`critical periods', but the relationship of body mass index (BMI) patterns during`critical periods' from childhood into adulthood with subsequent overweight and adiposity has not been previously investigated. BMI patterns during early childhood, pubescence and post-pubescence and their independent effects on overweight and body fatness at 35 ± 45 y of age were examined along with birth weight and the effects of adult lifestyle factors. METHODS: BMI parameters des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
223
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(239 citation statements)
references
References 22 publications
9
223
2
5
Order By: Relevance
“…Polynomial models to describe the patterns of change in BMI are also used. [11][12][13][14][15] Age at minimum BMI is derived from these models. Comparing different approaches, a recent study 15 concluded that estimating AR visually appears to best reflect the physiological basis of the AR.…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
See 2 more Smart Citations
“…Polynomial models to describe the patterns of change in BMI are also used. [11][12][13][14][15] Age at minimum BMI is derived from these models. Comparing different approaches, a recent study 15 concluded that estimating AR visually appears to best reflect the physiological basis of the AR.…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
“…4,8 This is similar to the generally reported mean values, varying between 5 and 7 years according to the population studied and the method used. [11][12][13][14][15][16] Prediction of adult fatness AR and adult fatness On average, AR takes place by the age of 6 years, but in individual cases, as shown in Figure 1, it may occur earlier or later. 8 These individual BMI patterns explain why, before AR, the child's BMI predicts adult fatness only poorly.…”
Section: Assessment Of the Age At Adiposity Reboundmentioning
confidence: 99%
See 1 more Smart Citation
“…2 These trends are likely to have major public health consequences since overweight or obesity status tracks from childhood to adulthood and there is emerging evidence that the precursors for diabetes and cardiovascular disease, some of which will be irreversible, already exist in overweight and obese children. [2][3][4][5][6][7] With respect to the tracking of measures of obesity across time, most studies have assessed correlations between body mass index (BMI) at different ages and found moderate correlations, 8,9 or have assessed how well being overweight or obese at one stage of the life course predicts being overweight or obese at a later stage. 6,[10][11][12][13] Few studies have examined the range of possibilities of patterns between two time pointsFthat is what proportion of those who are not overweight at the first time point have become overweight by the second and what proportion have remained not overweight and what proportion of those who are overweight at the first time point remain so by the second time point.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a burdening factor in all respects; it should become a public health priority in developed and developing countries, and it is from this perspective of prevention that the relationship between childhood obesity and young adult obesity has been investigated. Several studies have shown a tendency of those who are overweight or obese as children to remain overweight or obese as adolescents and adults (20)(21)(22)(23)(24)(25)(26)(27)(28) . However, much of the research has been conducted in high-income and predominantly Western countries, while only limited data are available for middle-or low-income countries and post-socialist countries (like Slovenia), which quickly and abruptly adopted capitalist economies and consumerist lifestyles, including eating habits and physical activity patterns.…”
mentioning
confidence: 99%